SDG 16 IN ASEAN: CASE STUDY ON BUILDING JUST AND INCLUSIVE SOCIETIES IN INDONESIA - Immanuel Ferdinand Barmandi; Ellya Dameria Enesca (Sociae Polites, 2023)
Achieving sustainable development has been confronted with many challenges both coming from the society and institution and what we mean by the institution is not limited by the state government only. Sustainable goals are expected from relations of mutual dependence between society and institutions (such as governments and international organizations), which we call the Sustainable Development Goals (SDGs) ratified by the member states of the United Nations. The idea of inclusive development is multifaceted, but ultimately it places an emphasis on the social, ecological, and political spheres of development at the national and regional levels. In this context, this paper addresses the question of what the challenges of building a just and inclusive society as part of the goal 16 of SDGs in ASEAN and then elaborate from specific case study of Indonesia on the challenge and obstacles of building a just and inclusive society. Although the main topic is discussing the challenge of the implementation, this paper also discusses how some regulations, structures, and values within the state have also been a driving factor of SDG 16 implementation. To analyze and frame the SDGs implementation and its challenges, the paper uses the social control theory from Durkheim. This paper finds that, while SDG implementation performs well in terms of social inclusion in the local community (a smaller area of development), it performs poorly in terms of human rights and tolerance. This paper suggests that there is a risk of failure in the actual implementation of SDG Goal 16 in a large and diverse country like Indonesia.